2006
DOI: 10.1016/j.chaos.2005.08.094
|View full text |Cite
|
Sign up to set email alerts
|

Cantor type attractors in stochastic growth models

Abstract: We study a one-sector stochastic optimal growth model where production is affected by a shock taking one of two values. Such exogenous shock may enter multiplicatively or additively. A result is presented which provides sufficient conditions to ensure that the attractor of the iterated function system (IFS) representing the optimal policy, is a generalized topological Cantor set. To indicate the role of the strict monotonicity condition on the IFS in this result, examples of attractors, which are not of the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Note that the condition α < φ required in Corollary 2 precludes the possibility of generating the standard, symmetric Sierpinski triangle with vertices(0, 0), (0, 1) and (1, 1) through (35), as its construction postulates that α = φ = 1/2 must hold. Hence, the attractor of (35) must always be a generalized Sierpinski gasket, that is, a Sierpinski gasket-like set whose prefractals 8 are composed by triangles that do not overlap for smaller values of α and φ, while they tend to overlap for larger values of either α or φ (see the examples in Section 5).…”
Section: Generalized Sierpinski Gaskets As Attractorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the condition α < φ required in Corollary 2 precludes the possibility of generating the standard, symmetric Sierpinski triangle with vertices(0, 0), (0, 1) and (1, 1) through (35), as its construction postulates that α = φ = 1/2 must hold. Hence, the attractor of (35) must always be a generalized Sierpinski gasket, that is, a Sierpinski gasket-like set whose prefractals 8 are composed by triangles that do not overlap for smaller values of α and φ, while they tend to overlap for larger values of either α or φ (see the examples in Section 5).…”
Section: Generalized Sierpinski Gaskets As Attractorsmentioning
confidence: 99%
“…9 However, by applying the main result of Section 2, Theorem 5, to the IFS (35) it is possible to establish the following sufficient condition for the singularity of the invariant measure. As there are three maps in the IFS (34), we can set only two out of the three probabilities associated to each map w i , say p 0 and p 1 , as the third must complement to 1:…”
Section: Singular Self-similar Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, at each iteration of the IFS (5) a hole appear in all components of the pre-fractal, so that in the limit a Cantor-like set appears as unique invariant set for the system [see, e.g., Falconer (1997Falconer ( , 2003, Mitra et al (2003), and Mitra and Privileggi (2004, 2006, 2009 for details]. ■ By asymmetric Cantor set here we mean a Cantor-like set in which the components in the left tail are smaller than those in the right tail; this is due to the different slopes of the linear maps φ i in (5), the slope of the lower map φ 0 being smaller than that of the upper map φ 1 , as illustrated in Figure 1 further on.…”
Section: The Modelmentioning
confidence: 99%
“…Mitra et al (2003) analysed a one-sector growth model with two random shocks whose optimal trajectory may converge to a singular distribution supported on a Cantor set, also characterising singularity versus absolute continuity of the invariant probability measure. Mitra and Privileggi (2004, 2006, 2009 further generalised that result by establishing conditions on the fundamentals under which the invariant probability happens to be supported on a Cantor set, and provided an estimate of the Lipschitz constant for the optimal policy. La and Marsiglio (2012) showed that the optimal path of a two-sector growth model subject to random shocks may converge to an invariant distribution supported on some fractal set.…”
Section: Introductionmentioning
confidence: 99%